An equal place : lawyers in the struggle for Los Angeles - Cummings, Scott L., 1969- (New York, NY : Oxford University Press, 2021)
In 'An Equal Place', Scott Cummings focuses on the movement for a living wage in Los Angeles and explores greater implications for the role of contemporary lawyers outside of the courtroom. The campaign to implement a living wage in L.A. was the most famous effort in the country, and advocates for it were largely successful, in part because they used the law to advance their agenda.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 11, 2021).
Keywords: Labor movement -- California -- Los Angeles; Working poor -- California -- Los Angeles; Labor policy -- California -- Los Angeles; Labor laws and legislation -- California -- Los Angeles